Masjid Raya Al-Mashun Medan sebagai Simbol Keagamaan dan Identitas Budaya Masyarakat Perkotaan - Nurharfani Nurharfani; Neila Susanti (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The Al-Mashun Grand Mosque in Medan serves not only as a place of worship for Muslims but also represents a religious symbol and cultural identity for urban communities in Medan. This study aims to examine the role of the mosque in the socio-cultural context, and how its existence reflects the religious values and ethnic Malay identity that are strongly embedded in its architecture and socio-religious practices. Using a qualitative approach and data collection techniques through interviews, field observations, and literature studies, this study found that the Al-Mashun Grand Mosque possesses a strong spiritual and cultural appeal. The mosque's architecture, which combines Middle Eastern, Indian, and European elements, serves as a symbol of Islamic splendor in the midst of a modern city. Its magnificent design and rich ornamental details reflect a valuable cultural heritage and attract visitors from various backgrounds. Furthermore, the mosque serves as a center for religious activities and a religious tourism destination, strengthening Islam's position in urban public spaces. Various social activities, such as religious study groups, Islamic holiday celebrations, and community empowerment programs, are held at the mosque, making it an important hub for social interaction. These findings indicate that the mosque is not only a place of worship but also a symbolic space that strengthens the identity and existence of local culture within the dynamics of urban society. The existence of the Al-Mashun Grand Mosque contributes to the formation of a harmonious and respectful community and serves as an example of how a place of worship can serve as a bridge between tradition and modernity in an urban context. Thus, the mosque serves not only as a spiritual sanctuary but also as a center for strengthening social and cultural values important to the people of Medan.